Kemampuan Komunikasi Matematis melalui Pendekatan SAVI (Somatic, Auditory, Visual and Intellectual) pada Siswa SMPN 1 Unggul Darul Imarah - Ikramuna, Divia (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
The objectives of this study were: (1) to determine the mathematical communication skills of students of SMPN 1 Unggul Darul Imarah after being taught using the SAVI approach; (2) to determine the mathematical communication skills of students who are taught using the SAVI approach and students who are taught using conventional learning. This study uses a quasi-experimental method. The population was all grade VII students of SMPN 1 Unggul Darul Imarah. Sampling using random sampling, which consists of two classes, namely class VII-6 as the experimental class and class VII-5 as the control class. Data collection used a test sheet of mathematical communication skills. Data analysis using t-test. The results of the study were: (1) based on the results of the t-test, it was found that the students' mathematical communication skills taught by the SAVI approach were better than those taught by conventional learning in class VII SMPN 1 Unggul Darul Imarah; (2) based on the comparison of the results of the pre-test and post-test, it shows that there is a positive influence on mathematical communication skills after being taught with the SAVI approach.